Myocardial damage biomarkers and the first case of macrotroponin I detection in endurance athletes - M. S. Smirnov; V. V. Dorofeykov; N. D. Golberg; E. V. Kurochkina (Acta Biomedica Scientifica, 2023)
Background. High levels of cardiac troponin in the blood indicates myocardial injury, including those caused by intense exercises. Recent studies have shown that an elevation in the troponin concentration in the patients can be caused by the macrotroponin circulation. There is no data in the scientific literature describing this problem in athletes.The aim. To identify the cases and possible causes of high blood levels of cardiac markers in athletes before and after endurance exercises.Materials and methods. The study was conducted on 11 male cross-country skiers aged 15–21 years. The study included two stages: the first was conducted at the end of the preparatory period (November, 2020–2021), the second – in the middle (March) of the 2020–2021 competitive period. At each stage, two blood samples were taken from a vein: the first – in the morning on an empty stomach after a day of rest, the second – 12–14 hours after a high-intensity exercise. In the blood serum, the activity of total creatine kinase (CK), weight concentration of the cardiac isoenzyme of creatine kinase (CK-MB), and concentration of high sensitive troponin I (Tn) were measured.Results. The activity of CK in athletes exceeded the upper limit threshold, and decreased from the preparatory (November) to the competitive (March) period. The concentration of CK-MB in response to exercise increased by 2 times and was not accompanied by the signs of myocardial injury. The most sensitive indicator, responsive to physical activity, was troponin I. However, the highest elevation of Tn in blood of one athlete, both before and after the exercise, was associated with the presence of macrotroponin without signs of myocardial injury.Conclusions. An increase of muscle tissue injury biomarkers in blood, including the heart muscle (CK, CK-MB, and Tn), by 2–4 times is a typical reaction for the body of a cross-country skier to an intense exercise. High levels of troponin in the blood, both before and after training or competition, may be associated with the presence of macrotroponin.